Interruptions versus breaks: The role of cue utilisation in a simulated process control task. Issue 2 (29th November 2020) - Falkland, Emma C.; Wiggins, Mark W.; Westbrook, Johanna I.
Abstract: Although interruptions and breaks are similar insofar as they both offer a momentary recess from the primary task, the premise for the activity in which the operator engages differs. Interruptions impose the requirement to direct resources to complete a task, while breaks offer the opportunity for suspended goal rehearsal. The aim of this study was to investigate differences in resumption lags following "interruptions" and "breaks, " and whether cue utilisation moderates this relationship. Seventy‐nine university students completed an assessment of cue utilisation and managed scheduled and unscheduled interruptions and breaks during a 35‐min rail control simulation. The analyses revealed that participants who recorded higher cue utilisation recorded shorter resumption lags following scheduled, rather than unscheduled interruptions. Participants who recorded lower cue utilisation recorded shorter resumption lags following breaks compared to interruptions, irrespective of the administration. The results suggest that scheduled interruptions and breaks offer the opportunity for suspended goal rehearsal.